Essentials of woodworking - Griffith, Ira Samuel, 1874-1924; Lawrence, Edwin Victor (Salt Lake City, UT : Project Gutenberg, 2023)
"Essentials of Woodworking: A Textbook for Schools" by Ira Samuel Griffith is an educational guide on woodworking techniques written in the early 20th century. This textbook is designed for students and educators, providing comprehensive instructions on tools, processes, and techniques essential for woodworking. Its content is structured to facilitate both theoretical understanding and practical application, suited for a range of educational settings from grammar schools to colleges. The opening of the book begins with the author's preface, addressing the significance of having a dedicated textbook for woodworking, which he believes should be studied with equal diligence as more traditional academic subjects. Griffith emphasizes that students need not follow a linear study of the text; instead, it's to be approached topically based on specific projects or tools in use. Following the preface, the introduction highlights the importance of maintaining tools in optimal condition and cultivating habits of orderliness and carefulness in woodworking practice. This establishes a strong foundation for the chapters that follow, which detail various tools, their uses, and techniques for effective woodworking. (This is an automatically generated summary.)
This book on woodworking contains notes and working directions omitted from 'Correlated courses in woodwork and mechanical drawing' by the same author, #68118.
Release date is 2023-10-12
Aaron Adrignola, Harry Lamé and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Woodwork (Manual training)